2020
DOI: 10.1155/2020/8850221
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Maximum Particle Diameter on the Mechanical Behavior of Soil‐Rock Mixtures

Abstract: With the steady development of the development of the western region in China, the construction of mountain highways has developed rapidly, and the soil-rock mixed filler, as an excellent filler, is widely used in the subgrade filling of mountain highways. Unlike ordinary fine-grained soil, the source of the soil-rock mixtures (S-RMs) is not unique, and the particle size difference is large and the water content is not uniform, resulting in very complicated mechanical properties. But the current highway embank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Many scholars believe that the content of "rock blocks" and their size distribution are the main structural characteristic features of S-RM, which mainly control its mechanical properties (Casagli et al, 2003;He et al, 2020). In-situ and laboratory tests show that the shear strength of S-RM is akin to that of the rock blocks alone when the proportion of rock blocks is higher than a certain threshold, and is basically that of the fine soils when the proportion of rock blocks is less than a certain threshold, the friction angle of S-RM increases with the increase of proportion of rock blocks (Donaghe and Torrey, 1979;Vallejo and Mawby, 2000;Cen et al, 2017;Gao et al, 2018;Wang et al, 2018;Song et al, 2020;Dong et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars believe that the content of "rock blocks" and their size distribution are the main structural characteristic features of S-RM, which mainly control its mechanical properties (Casagli et al, 2003;He et al, 2020). In-situ and laboratory tests show that the shear strength of S-RM is akin to that of the rock blocks alone when the proportion of rock blocks is higher than a certain threshold, and is basically that of the fine soils when the proportion of rock blocks is less than a certain threshold, the friction angle of S-RM increases with the increase of proportion of rock blocks (Donaghe and Torrey, 1979;Vallejo and Mawby, 2000;Cen et al, 2017;Gao et al, 2018;Wang et al, 2018;Song et al, 2020;Dong et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…To assess the stability of such natural and artificial geostructures, several researches have investigated the S-RM shear response, showing that the shear strength of S-RMs is mainly controlled by the volumetric block proportion (VBP) (Medley and Rehermann 2004;Xu et al 2011;Kalender et al 2014;Napoli et al 2018aNapoli et al , b, 2019, but is also affected by the moisture content (Xu et al 2007;Li et al 2020), block grain size distribution (Hamidi et al 2012;Zhang et al 2016a, b), block size ( He et al 2020;Christoph et al 2021) and block orientation (Lindquist 1994;Khorasani et al 2019). In addition, for the block shape, Graziani et al (2012) found that the friction angle of S-RM is higher when the blocks are triangular, followed by rectangular and then prismatic blocks.…”
Section: Introductionmentioning
confidence: 99%
“…However, in fillers with large differences in the filler particle size, it is difficult to establish the linear correlation between roller measurement values and in situ measurements due to the large discreteness [27]. It is not convenient to diagnose the compaction quality by the target value.…”
Section: Introductionmentioning
confidence: 99%